Anatomy of the aortic segmental arteries—the fundamentals of preventing spinal cord ischemia in aortic aneurysm repair - Pruidze, Paata; Weninger, Jeremias T.; Didava, Giorgi; Schwendt, Karoline M.; Geyer, Stefan H.; Neumayer, Christoph; Nanobachvili, Josif; Eilenberg, Wolf; Czerny, Martin; Weninger, Wolfgang J. (Frontiers in Cardiovascular Medicine, 2024)
ObjectiveSpinal cord ischemia due to damage or occlusion of the orifices of aortic segmental arteries (ASA) is a serious complication of open and endovascular aortic repair. Our study aims to provide detailed descriptions of the proximal course of the ASAs and metric information on their origins.Materials and methodsInitially, 200 randomly selected, embalmed cadavers of human body donors were anatomically dissected and systematically examined. On macroscopic inspection, 47 showed severe pathologies and were excluded. Of the remaining 153, 73 were males and 80 females.ResultsIn total, 69.9% of the aortae showed 26–28 ASA orifices. In 59.5% the most proximal ASA, at least unilaterally, was the third posterior intercostal artery, which originated from the descending aorta at approximately 10% of its length. In 56.2%, the left and right ASAs had a common origin in at least one body segment. This mainly affected the abdominal aorta and L4 in particular (54.2%). The ASAs of lumber segments 1–3 originated strictly segmentally. In contrast, in 80.4%, at least one posterior intercostal artery originated from a cranially or caudally located ipsilateral ASA. Such an arrangement was seen along the entire thoracic aorta. Further descriptions of variants and metric data on ASA orifices are presented.ConclusionOur large-scale study presents a detailed topographic map of ASAs. It underscores the value of preoperative CT councils and provides crucial information for interpreting the results. Furthermore, it aids in planning and conducting safe aortic intervention and assists in deciding on single- or two-staged stent graft procedures.